Pengaruh Rentabilitas, Efisiensi, dan Likuiditas Terhadap Kecukupan Modal Bank Umum Syariah: Study Pada PT Bank Syariah Mandiri Tbk - Fatimah, Siti (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2014)
The Influence of Rentability, Efficiency, Liquidity To Capital Adequacy Ratio in Islamic Bank: Study at PT Bank Syariah Mandiri. The aim of this study is to analyze the influence of rentability (ROA), efficiency (BOPO), and liquidity (FDR) to Capital Adequacy Ratio (CAR) in short-run and long-run. The method analysis that used in this study is VECM method. The result was shown that ROA had a significant negative influence to CAR, BOPO had a significant positive influence to CAR, and FDR had a significant negative influence to CAR. There were a long-run correlation between BOPO and FDR to CAR, and there were a short-run correlation between ROA, BOPO, FDR to CAR. DOI:10.15408/aiq.v6i1.136810.15408/ijies.v6i1.1367